ETHNOPSYCHOLINGUISTIC ASPECT OF REGIONAL LANGUAGE CONSCIOUSNESS - Balyasnikova, O.V.; Cherkasova, G.A.; Stepanova, A.A.; Ufimtseva, N.V. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The article analyzes the phenomenon of “regional language consciousness” relying on data of psycholinguistic (associative) experiment held with the Tatar bilingual, residing in the Republic of Tatarstan. The experimental data are compared with the materials of the regional Russian associative dictionary (EVRAS) to determine the similarities and differences in the content of the image of “power” in the language consciousness of the respondents - the Tatar and the Russian. Based on the materials of the pilot study conducted in 2015, we outline the prospective for the analysis of “regional language consciousness” taking into account ethnic factors, language, bilingualism, and region of residence. One of the possible ways of presenting the results is a semantic image of relevant structured semantic areas and subareas in accordance with the characteristics of the data and the general objectives of the research project.